2013
DOI: 10.1016/j.polymer.2013.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and properties of plasticised chitosan-based exfoliated nano-biocomposites

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 41 publications
(44 reference statements)
8
26
0
1
Order By: Relevance
“…The addition of MMT in MS/20G films deteriorated the tensile strength and stiffness but the elongation at break was maintained/enhanced. This result is in agreement with previous studies where it was suggested that MMT layers are drifted with G molecules during the elongation process. This phenomenon was also observed in the case of MS/G/PVOH/MMT samples.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The addition of MMT in MS/20G films deteriorated the tensile strength and stiffness but the elongation at break was maintained/enhanced. This result is in agreement with previous studies where it was suggested that MMT layers are drifted with G molecules during the elongation process. This phenomenon was also observed in the case of MS/G/PVOH/MMT samples.…”
Section: Resultssupporting
confidence: 94%
“…The increase in d‐spacing of MS/20G/MMT in comparison to MS3MMT confirms that glycerol favors the opening of MMT interlayer space and supports the incorporation of MS chains into the MMT's platelets . In our case, sharp and intense 001 reflection in XRD patterns of MS/G/MMT films corresponds to well organized silicate layers, in other words to intercalated nanocomposite structure.…”
Section: Resultssupporting
confidence: 76%
“…Supporting these findings, it has been previously reported that using glycerol as a plasticizer makes films more hydrophilic and increase the biodegradation rate of films by microbial activity [21,22]. Xie et al [14] have reported that plasticized chitosan-based nanobiocomposites degraded more easily than unplasticized chitosan due to the presence of glycerol.…”
Section: Thermal Analysissupporting
confidence: 53%
“…Dean et al [13] have reported that addition of nanoclay to chitosan films 81 had no significant effect on degradation both in soil and composting conditions, which was prepared using melt processing method with or without glycerol as a plasticizer. Another study by Xie et al [14] which has reported that the addition of glycerol and unmodified nanoclay caused to increase of biodegradation degree, mainly related to the addition of unmodified nanoclay. As a consequence, the chitosan biodegradation mechanism in a composting environment is not well defined yet.…”
Section: Introductionmentioning
confidence: 96%
“…Although this method is appropriate for preliminary study, it is not feasible on an industrial scale as large amounts of energy are required to evaporate the solvent, and the processes involved in power handling large volumes of film-forming solutions are complex (Guti errez & Alvarez, 2017). Polymer and food manufacturers thus prefer to produce thermoplastic starch (TPS) materials using techniques such as extrusion (Xie et al, 2013), which does not require the use of a solvent as starch gelatinization is achieved by the mechanical (shear force) and thermal energy produced during processing (Alam, Pathania, & Sharma, 2016;Zhang, Wang, Zhao, & Wang, 2013). In addition, extrusion is a continuous system that can be managed by only a few operators, thus optimizing the manufacturing process.…”
Section: Introductionmentioning
confidence: 99%